Peran nature-based solution dalam penanggulangan banjir dan ketahanan iklim perkotaan: kajian literatur ilmiah - Angghita, Lintang Jata; Tahalele, Marcio; Kalmah, Kalmah (Jurnal Pengelolaan Lingkungan Berkelanjutan (Journal of Environmental Sustainability Management), 2026)
Hydrometeorological disaster management in urban areas presents significant challenge in urban and environmental governance. Nature-based solutions (NbS) offer an innovative approach that utilizes natural ecosystem functions to reduce the risks of hydrometeorological disasters and enhance climate resilience in urban environments. This study aims to analyze the interrelationships among NbS components withspecific focus on flood control and risk reduction in urban areas. The analysis was conducted through literature review and bibliometric analysis of 15 relevant scientific publications from the past decade. The results were visualized and mapped using VOSviewer software. The network mapping and visualization reveal that topics related to NbS are strongly associated with climate change, hydrometeorological disasters, ecosystems, urban governance, biodiversity, and sustainability. The implementation, effectiveness, and policy dimensions of NbS highlight ongoing challenges in performance evaluation that are essential to optimize their application. Based on the literature review, to reduce hydrometeorological disaster risks, the major challenges in implementing NbS depend on performance assessment, community participation, and multi-sectoral collaboration.